Nucleocapsid (NP) and Phospho-(P) Proteins of Newcastle Disease Virus: Identification of Regions on NP That Form Particles and Interact with P - Kho, Chiew Ling (2003)
The nucleocapsid protein ( NP) of Newcastle disease virus (NDV) plays an important role in the replication of the viral genomic RNA. The NP is closely associated with the viral phosphoprotein ( P) and this association is crucial in ensuring the specific binding ofNP to the viral RNA. In order to have a better understanding of the structure and functions of the NP, deletion mutagenesis was carried out to characterise and localise regions involved in NP-NP and NP-P interactions. The NP and a fusion derivative (NPcfus) containing a hexa histidine tag at its C-terminus were produced abundantly in Escherichia coli. These proteins were fractionated on sucrose gradient centrifugation and microscopic analysis showed that both the NP and NP cfus proteins self-assembled predominantly into ring-like particles with the diameter of 24 ± 2 nm around a central hole of 7 ± 1 nm. Some of these ring-like particles stacked together to form herringbonelike particles which are heterogenous in length with a diameter of 20 ± 2 nm and a central hollow of 5 ± 1 nm. Fusion of the C-terminal end to 29 amino acids inclusive of the myc epitope and His-tag did not impair ring assembly but inhibit the formation of the long herringbone particles. Immunogold labelling of the ring-like particles with the anti-myc antibody showed that the Cterminus of the NPcfus protein is exposed on the surface of the particles.